Effect of the dietary inclusion of the growth promoter avoparcin on the performance and carcass characteristics of growing goat kids - BABIDIS (Β. Μ. ΜΠΑΜΠΙΔΗΣ) V. A.; FLOROU-PANERI (Π. ΦΛΩΡΟΥ-ΠΑΝΕΡΗ) P.; KUFIDIS (Δ. ΚΟΥΦΙΔΗΣ) D.; SPAIS (A.B. ΣΠΑΗΣ) A. B. (Journal of the Hellenic Veterinary Medical Society, 2018)
A trial was conducted with 32 indigenous goat kids (Capra prisca) 8,5 weeks old to examine the effectiveness of dietary avoparcin as growth promoting factor. The kids were randomly allocated into two groups (control- and avoparcin group with initial mean body weight of 11,61 ±1,16 kg and 11,57±1,47 kg, respectively) comprising of 16 kids (8 male and 8 female) each. For a period of 12 weeks, kids in the control group were given lucerne (alfalfa) hay (mean daily consumption 170 g/head) and an appropriate compound diet (given ad libitum), while kids in the avoparcin group were fed the same diet except that the compound diet was supplemented with avoparcin (20 mg/kg). Avoparcin supplementation significantly (P<0.05) improved final mean body weight by 10.57% (19.24 ± 2.33 kg vs. 17.40 ± 2.30 kg), body weight gain (BWG) by 32.30% (7.66 ± 1.42 kg vs. 5.79 ± 1.74 kg), mean daily feed consumption in dry matter basis (DM) by 14.24% (551.80 ± 31.60 g DM vs. 483.02 ± 28.94 g DM), feed conversion ratio by 13.62% (6.09 ± 0.47 kg DM consumption/kg BWG vs. 7.05 ± 0.56 kg DM consumption/kg BWG) and carcass weight by 14.86% (11.44 ± 1.48 kg vs. 9.96 ± 1.76 kg). Moreover, no significant differences (P>0.05) were noticed neither in carcass yield and carcass chemical composition nor in percentages of small intestine-, major omentum-, lung-,heart-, liver- and spleen weight in the body weight.